Comparison of the Short Time Effect of an Oral Hygiene Education in Four Sessions via Quantitative Light-Induced Fluorescence Technology Versus Disclosing Agents in Children: A Randomized, Crossover Clinical Trial - Sangkyu Han; Seong Jin Kim; Taeyang Lee; Hoi-In Jung; Ko Eun Lee; Je Seon Song (MDPI AG, 2024)
Objectives: The aim of this study is to compare the effectiveness of Qscan plus™ (AIOBIO, Seoul, Korea) based on quantitative light-induced fluorescence (QLF) technology and disclosing agents in oral health programs in children. Methods: A randomized crossover study was conducted for Korean children aged 6-11 years. Fifty-eight participants (29 to use Qscan plus™ first and 29 to use the disclosing agent first) were enrolled in this study. The participants were randomly divided into two groups. One group was assigned to brush with Qscan plus™, while the other group brushed with disclosed plaque visualization. One month later, the groups switched procedures. A total of 39 participants were analyzed, excluding those lost during the trial. There was no adverse event during the trial. The patient hygiene performance (PHP) index was used to assess oral hygiene status, and questionnaires about oral health behavior and attitude were completed. The data were analyzed using repeated-measure analysis of variance, with a significance level of p < 0.05. Results: The PHP score decreased significantly on post-brushing and follow-up compared to baseline in both methods (p < 0.001), but there was no significant difference between the two methods. After oral hygiene education, participants' brushing time increased, and their oral care attitudes improved. More participants preferred the Qscan device to the disclosed plaque visualization because it is more easily noticeable. Conclusions: The Qscan device has a similar educational effect as disclosing agents, and can be used as a supplementary tool to encourage children in oral hygiene education.